2006
DOI: 10.1158/0008-5472.can-06-0127
|View full text |Cite
|
Sign up to set email alerts
|

A Hypermutation Phenotype and Somatic MSH6 Mutations in Recurrent Human Malignant Gliomas after Alkylator Chemotherapy

Abstract: Malignant gliomas have a very poor prognosis. The current standard of care for these cancers consists of extended adjuvant treatment with the alkylating agent temozolomide after surgical resection and radiotherapy. Although a statistically significant increase in survival has been reported with this regimen, nearly all gliomas recur and become insensitive to further treatment with this class of agents. We sequenced 500 kb of genomic DNA corresponding to the kinase domains of 518 protein kinases in each of nine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
332
0
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 396 publications
(360 citation statements)
references
References 19 publications
(29 reference statements)
17
332
0
5
Order By: Relevance
“…MGMT expression in GBM occurs in approximately 40% to 50% of patients with GBM, yet temozolomide resistance is almost universal, demonstrating that other mechanisms of temozolomide resistance are operating (17,45,46). MMR deficiencies are also documented in recurrent patients with GBM (19,20,47). As much as 25% of recurrent GBMs exhibit MMR deficiencies (48).…”
Section: Discussionmentioning
confidence: 99%
“…MGMT expression in GBM occurs in approximately 40% to 50% of patients with GBM, yet temozolomide resistance is almost universal, demonstrating that other mechanisms of temozolomide resistance are operating (17,45,46). MMR deficiencies are also documented in recurrent patients with GBM (19,20,47). As much as 25% of recurrent GBMs exhibit MMR deficiencies (48).…”
Section: Discussionmentioning
confidence: 99%
“…13 Clonal evolution is also supported by findings that various drug-resistant clones are observed after some cancer therapies, such as treatment with the alkylating agent temozolomide or the tyrosine kinase inhibitor imatinib. [57][58] Finally, several studies of various cancers have shown that the patterns of genetic alterations seen between primary tumors, metastases, and recurrences match what is expected from clonal evolution. Within individual patients, most mutations in primary tumors and metastases are identical, but some are unique to each; increasing degree of tumor cell chromosomal aberration correlates with more malignant properties; and recurrences contain the mutations seen before in primary tumors along with additional ones.…”
Section: The Cancer Stem Cell Hypothesismentioning
confidence: 93%
“…Although elevation of AKT activity is seen more frequently than PTEN mutation in gliomas and medulloblastomas (Schlegel et al, 2002;Hartmann et al, 2006), mutations causing increased activity of any AKT isoform have not been observed frequently. AKT1 amplification has been reported in various human cancers, including a single case of gliosarcoma (Knobbe and Reifenberger, 2003) and AKT3 mutation has been reported in a single case of glioma (Hunter et al, 2006); however, the consequence of this missense mutation (G171R) on the activity of the enzyme is unknown. While AKT2 amplification has been observed frequently in head and neck tumors, as well as pancreatic, ovarian and breast cancers (Bellacosa et al, 1995;Cheng et al, 1996;Pedrero et al, 2005;Nakayama et al, 2006), it has not yet been described in primary human brain tumors, although studies indicate it may be overexpressed and drive tumorigenicity in some glioma cell lines (Pu et al, 2006).…”
Section: Pi3k Pathway Involvement In Brain Tumorsmentioning
confidence: 99%